Attitudes of preservice instructional designers towards online collaborative learning - Özdemir, Oğuzhan; Erten, Pınar; Kazu, İbrahim Yaşar (Sakarya University, 2016)
Flexibility and usability in efficient instruction design model depend on the usage of information and communication technologies which will provide sufficient performance to students in the process. In instruction design process, necessity of individual study and collaborative group events occurred, drifting apart from traditional instruction (Morrison, Ross, Kalman and Kelp, 2011). For this reason, defining attitudes of preservice teachers towards online collaborative learning (OCL) has importance. Attitudes of preservice instruction designers towards OCL are tried to be defined with this study. Population of study prepared according to descriptive survey model is formed of preservice teachers who are instructional designers and study in Computer and Instructional Technologies departments. Sample of the study is formed of students who study in Computer and Instructional Technologies departments of a university. Online collaborative instruction attitude scale of Korkmaz (2012) was used to define attitudes that are positive or negative interaction levels of students (Edwards, 1983) towards online collaborative instruction environment in the study. In this way, attitudes are assessed with inferences made out of reactions towards their real feelings behaviors and psychological reaction to a series of sentences or a list of adjectives of individuals (Anderson, 1991). That the students are affected in a positive way in online collaborative instruction environment is defined. The students within the scope of study stated that their interest in lesson has increased and the lessons that they find difficult are more interesting and will be learnt better. It is supported that online collaborative instruction environments have positive effects on individuals as a result of many studies (Daradoumis, Martínez-Monés ve Xhafa, 2006; Brindley, Walti and Blaschke, 2009; Janssen, Erkens, Kirschner and Kanselaar, 2009; Blake and Scanlon, 2013). It is ensured that the lessons should be prepared in conformity with online collaborative environments. Besides, application of instruction in various stages should be supported. Especially in education stages that train teachers, this kind of education methods and their privileges should be introduced to students and students should be trained in quality to apply these in their working life by including them in the programs. © The Turkish Online Journal of Educational Technology.
Keywords: Attitudes; Online collaborative learning; Preservice instructional designers